China modernizes : threat to the West or model for the rest? - Peerenboom, Randall (Oxford Oxford University Press, 2008)
Two sharply contrasting views of China exist today; one of a rising superpower, and the other of an anachronistic, authoritarian regime. So which is the real China? Randall Peerenboom offers a controversial, first-hand account of modern China focusing on its economic, political and legal attributes within the context of the developing world. - ;Two sharply contrasting views of China exist today. On the one hand a rising superpower predicted to have the largest economy in the world by mid century, on the other hand a brutal, anachronistic and authoritarian regime, a threat to geo-stability and
Keywords: Derechos humanos -- China; Democracia -- China; China -- Situación económica -- 2002-; China -- Política y gobierno -- 2002-